THE EFFECT OF CORRECTIVE FEEDBACKS ON L2 STUDENTS’ WRITING PERFORMANCE - Natalia Faradheta Putri; Giovanni Chun Long Ma (Universitas Islam Sumatera Utara, 2022)
In the past years, teachers have been made to assume that corrective feedback benefits students’ writing improvement. Corrective feedback as “any information provides information on the result of behaviour. However, a growing body of research has been reinvestigating the effectiveness of corrective feedback as a result of John Truscott’s claim of its inefficiency. This paper aims to expand the related study on written corrective feedback to find corrective feedback with a significant positive effect on students’ writing performance. This experimental study obtained the data from sixty-six homogeneous L2 students which were equally divided into three groups. The first group was given explicit correction feedback, the second group was given metalinguistic clue feedback, and the last group was the control group. The result showed that the explicit correction was more effective compared to metalinguistic but the fact that the participants tend to perform better even without receiving any correction made the small effect of explicit correction to be questioned.